The internationalization of higher education - local tendencies and realities in the education of students of engineering and natural sciences in a mexican a university -a case study. - Dörfer, Claudia; Araiza Vázquez, María de Jesús (2012)
The present work is part of a greater research project which is currently in the stage of exploration. The project aims at exploring the education of students abroad seen from their perspective during their stay abroad. Since the end of the 20th century, higher education institutions (HEI) in Mexico have reinforced various strategies to meet national and international requirements implicated by processes of globalization. For that reason, some HEI have been reacting making use of the opportunities to implement students exchange programs, to prepare their students in foreign countries. Based on a literature review, the present research aims at giving answers to questions as the following: What characterizes the internationalization of higher education in a Mexican university? What are the tendencies and in which way do they influence our local educational sector? The special interest of this exploratory research work is focused on case studies in which statements of pre-graduate students of engineering and natural sciences studying in European universities give a particular insight into the process of internationalization and some of its consequences. This work intends to describe the situations with which these students are confronted during and after a stay abroad as well as to retain the students’ perspective about the personal and professional conditions and circumstances they experienced during and after their stay abroad. In these interviews answers can be found to questions regarding motivations, reasons and objectives for studying abroad, special situations. Moreover, there are questions about the students’ expectations when coming back, about the types of situations and circumstances they found themselves confronted with when coming back to their educational environment in Mexico. With all this we hope to be able to contribute to improve educational processes, and to make findings from the point of view of its main actors as well as to support administrative decision making the moment when students enter academic exchange programs.